Investigating Direct Torque Control of Six-Phase Induction Machines Under Open Phase Fault Conditions - R. Kianinezhad; A. Hajary (AUT Journal of Electrical Engineering, 2017)
This paper presents analysis and evaluation of classical direct torque control(DTC), for controlling a symmetrical six phase induction motor (SPIM) under open phasefault conditions. The machine has two three-phase windings spatially shifted by 60 electricaldegrees. The strategy of the proposed method consists of choosing the switching modesaccording to the configuration of living phases in such a way that it generates vectors thathave higher amplitude in α-β plane while their projections on z axis give zero or near zeroamplitude vectors. The goal is reducing parasitic currents and torque ripples of SPIM underfaulty mode. Based on the theoretical analysis, it will be shown that in the open phase faultconditions, the only non-pulsating operation is obtained by opening the fault three-phasewinding. Experimental test results are provided o support theoretical analysis in open phasefault conditions for SPIM.